2014
DOI: 10.5223/pghn.2014.17.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Clonazepam Treatment of Pathologic Aerophagia in Children with Mental Retardation

Abstract: PurposePathologic aerophagia (PA) may lead to bowel perforation or volvulus in mentally retarded patients. The authors investigated the effects of clonazepam on the management of PA in children with severe to profound mental retardation (MR).MethodsThis study was undertaken as a retrospective case analysis of 21 PA patients with MR who were followed for over 12 months and diagnosed as having PA. Patients were assigned to two management groups, that is, to a clonazepam randomized open-labeled, treatment group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…No other aetiological factors were identified. Although there are reports of beneficial effects of clonazepam in PA in patients with intellectual disability (Lee et al ., ), our patient did not show any improvement. Behavioural or psychological interventions were impractical because of his severe cognitive impairment and communication difficulties.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…No other aetiological factors were identified. Although there are reports of beneficial effects of clonazepam in PA in patients with intellectual disability (Lee et al ., ), our patient did not show any improvement. Behavioural or psychological interventions were impractical because of his severe cognitive impairment and communication difficulties.…”
Section: Discussioncontrasting
confidence: 59%
“…It has also been suggested that PA may originate from a reflex‐induced swallowing due to unknown factors (Hwang et al ., ). It may occur as a result of involuntary paroxysmal cricopharyngeal sphincter openings of the oesophagus, like myoclonus (Hwang et al ., ) which may explain the benefits observed with clonazepam (Lee et al ., ). PA has also been reported in patients with autism, Rett syndrome and Tourette's syndrome (Frye & Hait, ; Hwang et al ., ; Van der Kolk et al ., ; Weil et al ., ).…”
Section: Review Of Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…The presence of such vicious cycle and the risk of acute abdomen in patients with SMID, in whom abdominal distension is merely recognized as "constipation", should be noted. Venting gas through a nasogastric tube or via a gastrostomy, use of a mouthpiece to inhibit deglutition, and benzodiazepines have been reported to be effective for the reduction of aerophagia [31][32][33]. However, air venting via the gastrostomy was not effective in patient 1.…”
Section: Discussionmentioning
confidence: 99%